Evaluación ex-ante del impacto del genotipo de arroz L23 en la Altillanura plana colombiana - Marín Salazar, Diego Armando; Andrade, Robert Santiago; Labarta, Ricardo Antonio; Vásquez Urriago, Ángela Rocío; Caicedo Guerrero, Samuel (Universidad de Costa Rica, 2019)
Introduction. The Colombian Altillanura is going through a process of transformation, marked by the expansion of its agricultural border. In the region, it is being implemented a research agenda that seeks to develop and validate promising technologies for the improvement of productivity and sustainability of agricultural production systems. Economic evaluation plays an important role in prioritizing activities, allocating resources, and guiding agricultural research towards rural development objectives. Objective. The objective of this work was to implement an ex-ante economic evaluation to estimate the results and potential impacts of the new promising L23 rice line improved for the Colombian Altillanura. Materials and methods. The impact was measured on the L23 rice genotype, which was developed as a collaboration between the Colombian Corporation of Agricultural Research (AGROSAVIA) and the International Center for Tropical Agriculture (CIAT), for the Colombian Altillanura. The ex-ante evaluation combined a partial budgets analysis with information from experimental tests and economic surpluses model. Results. The two methodological approaches were consistent and showed that with the adoption of the L23 genotype at least 29.7%, a probability of 17.1 % could be achieved for rice producers in the Altillanura due to the expected increase in crop yield. However, a sensitivity analysis of the assumptions warns that a low potential level of adoption along with non-significant changes in yield would make the research and development of the new genotype economically unfeasible. Conclusion. For the research, development and, introduction of the L23 rice genotype to be profitable, it is required a diffusion process that allows the reproduction of the seed and facilitates the access to producers, so that they can reach higher levels of adoption.